EVALUASI EFEKTIFITAS PEMBELAJARAN HYBRID PADA INSTITUSI PENDIDIKAN INSTIKI DENGAN DISCREPANCY EVALUATION MODEL - Aniek Suryanti Kusuma; I Gede Ratnaya; I Made Candiasa (UHN IGB Sugriwa Denpasar, 2022)
This research purpose to evaluate the effectiveness of the hybrid learning program at the INSTIKI Denpasar institution. This qualitative evaluative research uses the Discrepancy Evaluation Method model by Provus (1971) through 5 stages of design, installation, process, product, and cost-benefit analysis. Data were collected using interviews with Vice-Chancellor 1 for education, four lecturers and five students, observation, and documentation. Data analysis uses data collection, data reduction, data presentation, and verification. Based on the research, the objectives of the hybrid learning program were achieved. The results of the study found that the hybrid learning effectiveness program at the INSTIKI Denpasar institution was considered good with a description of the design stage, installation stage, stage on-campus that fulfilled eighty percent of the government's aspects, and stage four objectives were achieved so that it was of good value. In the comparison phase with other programs, each program is helpful but supports the other. Four gaps were found in the program: the lack of parental involvement in the classroom and the cessation of lecturer-to-lecturer activities. There is no combination of news and accompanying readings, caregivers participate in the program. Researchers suggest continuing this program with improvements